Heamatological and Serum Biochemical Estimates of Weaner Pigs Fed Enzyme Supplemented Tigernut (Cyperus esculentus) Chaff Based Diets (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study was carried out at the piggery unit of Alex Ekwueme Federal University Ndufu-Alike Ikwo, Abakaliki, Ebonyi State to evaluate the haematological and serum biochemical estimates of weaner pigs fed graded levels of tigernut chaff enzyme based diets. Sundried tigernut chaff (waste from tigernut processing) was collected from reputable tiger nut milk processors at Abakaliki, Ebonyi State, sun-dried for 5-7 days for the determination of proximate composition. Four experimental diets were formulated such that tigernut (Cyperus esculentus) chaff treated with multi-enzyme notably Growin ACT was included at 0%, 5%, 10% and 15% dietary levels coded (T1), (T2), (T3) and (T4) respectively. Data obtained from the study was subjected to the one-way analysis of variance (ANOVA) using general linear model of SPSS version. Results of the study showed that pigs fed enzyme supplemented tigernut chaff based diets showed significant (P